Influence of selenium combined with rice straw on the inhibition of copper phytotoxicity to pak choi. Issue 1 (31st December 2022) - Tran, Thi Anh Thu; Nguyen, Thanh Hung; Dinh, Quang Toan; Le, Trong Dieu Hien
ABSTRACT: This study aimed to explore the effects of Se combined with rice straw (RS) on alleviating Cu toxicity through the change of Cu bioavailability in soil. The growth parameters of pak choi, the total Cu concentrations in pak choi, the changes of Cu fractions in soils before planting and after harvest, and the bioconcentration and the translocation factors were determined. Results showed that Se application may detoxify Cu at excessive concentrations (200 mg/kg) by transforming mobile Cu fractions into semi-mobile and non-mobile Cu fractions (FEM-Cu, OM-Cu, and RES-Cu). The Cu concentrations in pak choi decreased and pak choi growth increased. Se also increased the Cu concentration in pak choi and promoted pak choi growth at low Cu concentration (50 mg/kg). The RS supplementation in Cu–Se co-exposure treatments can limit the absorption Cu in pak choi and enhance pak choi growth than only Cu–Se co-exposure treatments. This combination only affected the uptake of Cu by pak choi tissue but did not change the translocation efficiency from root to shoot. This study suggested that Se combined with RS plays an important role in preventing Cu uptake by plant tissues at excessive concentrations through transformations into immobile Cu fractions.